60.7k views
5 votes
How do you do this
2(f-3)+5=3(f-1)
Plz show work
Thx!

User Shryme
by
6.9k points

2 Answers

5 votes
So first, we need to distribute:


2(f-3)+5=3(f-1)

2f-6+5=3f-3

Then we simplify like terms that are on the same side of the equal sign:


2f-1=3f-3

Then we need to get the variable on one side. Let's subtract 2f from both sides:


-1=f-3

Then solve for f by adding 3 to both sides:


f=2

So now we know that f = 2.
User Musefan
by
6.6k points
6 votes
f=2 is the correct answer
How do you do this 2(f-3)+5=3(f-1) Plz show work Thx!-example-1
User Justine
by
6.6k points